A case of bilateral acute angle closure attack with some unusual features - Devi, Bhanu; Das, Rajiv Kr; Bhattacharjee, Supantha (International Journal of Research in Medical Sciences, 2016)
A 45 year old male presented with sudden severe pain, redness and marked diminution of vision in both eyes along with corneal oedema, pigmented KPs and raised IOP. After treatment with hyper osmotic agents, IOP came down and cornea became clear. Anterior chamber was shallow bilaterally with ring synechia. Gonioscopy revealed peripheral anterior synechiae in left eye and occludable angle in the right eye. Fundus examination was within normal limit. The patient was treated with antiglaucoma medications and steroid. Trabeculectomy was done in left eye with laser PI in the fellow eye. IOP came down within normal limits on subsequent visits with residual iris sphincter damage.